RvE1 Impacts the Gingival Inflammatory Infiltrate by Inhibiting the T Cell Response in Experimental Periodontitis - Alvarez, Carla; Abdalla, Henrique; Suliman, Salwa; Rojas, Paola; Wu, Yu-Chiao; Almarhoumi, Rawan; Huang, Ren-Yeong; Galindo, Mario; Vernal, Rolando; Kantarci, Alpdogan (Frontiers in Immunology, 2021)
Periodontitis is a chronic inflammatory disease associated with the formation of dysbiotic plaque biofilms and characterized by the progressive destruction of the alveolar bone. The transition from health to disease is characterized by a shift in periodontal immune cell composition, from mostly innate (neutrophils) to adaptive (T lymphocytes) immune responses. Resolvin E1 (RvE1) is a specialized pro-resolution mediator (SPM), produced in response to inflammation and to enhance its resolution. Previous studies have indicated the therapeutic potential of RvE1 in periodontal disease; however, the impact of RvE1 in the microbiome-elicited osteoclastogenic immune response remains uncharacterized. In the present study, we measured the impact of RvE1 on the gingival inflammatory infiltrate formation during periodontitis in a mouse model. First, we characterized the temporal changes of the primary immune cells infiltrating the gingiva by flow cytometry. Then, we evaluated the impact of early or delayed RvE1 administration on the gingival immune infiltration and cervical lymph node composition of immune cells. We observed a consistent inhibition of T cells -particularly effector T cells- and a protective effect on regulatory T cells (Tregs). Our data further demonstrated the wide range of actions of RvE1, its preventive role in the establishment of the adaptive immune response during inflammation, and bone protective capacity.